Capacity development for water reuse in in-formal partnerships in northern Namibia - Frick-Trzebitzky, Fanny; Kluge, Thomas; Stegemann, Stefan; Zimmermann, Martin (Frontiers in Water, 2022)
In central northern Namibia, challenges in water governance related to scarcity meet needs in capacity development on municipal levels. Reuse of treated water in agriculture forms a technical innovation in urbanizing arid regions, because it potentially contributes to both improving water availability and reducing pollution from waste water in arid regions. Governing this transformative approach entails a complexity of processes and actors at different levels and in a range of sectors. The aim of this research is to assess the potential of an informal municipal partnership to (a) support capacity development in implementation of innovation in urban water systems (here: water reuse), and (b) compensate for lack of coordination in governance. Establishing a municipal partnership for wastewater treatment was part of a living lab approach analyzing the potential for water reuse, in collaboration of an interdisciplinary team of researchers, municipal decision-makers, engineers and farmers. Findings show the potential and limitations in capacity development in municipal water governance by means of an informal partnership. The lessons learnt on establishing an informal municipal partnership for learning and capacity development in water governance provide valuable insights for water governance in both research and practice, in particular but not limited to the field of water reuse as means of transforming socio-hydrological relations toward sustainability. The research thus contributes to research on water reuse governance, and to transformative research on water in social-ecological systems.